Desenvolvimento tecnológico, caracterização e avaliação in vitro de micropartículas poliméricas contendo timomodulina - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
Thymomodulin (TMD) is a purified extract of the calf thymus consisting of a mixture of polypeptides obtained by the partial acid hydrolysis of the gland. It has an immunomodulatory action, mainly in stimulating the functions of T, B and NK cells, promoting the improvement of the immune response of patients in various diseases, cancer, AIDS and allergies, being considered an important ally in combating herbs. Treatment with TMD generally requires its administration in an injectable form and for a prolonged period of use, resulting in low patient compliance with treatment, in addition to being restricted as pharmaceutical forms available as drug therapy. Therefore, modified-release systems can be developed to create routes of administration accompanied by a reduction in treatment time while maintaining effective efficacy. In view of this, this work aims to develop and evaluate polymeric microparticles containing TMD, using the hydroxypropylmethylcellulose polymers and poloxamer 188, by spray-drying method, in the due amounts of 5, 10 and 20% of drug, in order to obtain a mucoadhesive system that provides opportunities an alternative route of administration to parenteral. The polymeric microparticles were characterized by means of morphological, spectroscopic and thermal studies. The polymeric microparticles containing TMD were successfully corrected by the chosen method and spherical and / or distorted, with a smooth, rough or concave surface, with an average particle size of approximately 10 μm. The analytical method chosen for the determination of TMD in microparticles was selective and linear. As encapsulation efficiency formulations between 84.4 and 98.6%. X-ray diffraction confirms that the encapsulation method was efficient and the drug is primarily in molecular dispersion in the microparticle matrix. Fourier transform infrared spectra ensured that the microencapsulation process did not result in links between the TMD and the polymers. A thermal analysis shows the protection that the polymeric system gave to the polypeptide extract, reducing the events of thermal degradation of the drug. The in vitro release of the microparticles of the two formulations with the highest drug concentration (MT10 and MT20), at pH 6.8, revealed a slow, gradual and progressive release profile with similar dissolution efficiencies (7.75 and 7.79%) indicating a prolonged release of the drug. Therefore, the results provide an experimental basis for considering microparticles containing TMD prepared by spraydrying as a viable strategy for the development of new pharmaceutical forms for a modified release of the TMD immunomodulator for application in biological therapies.
Keywords: Polipeptídeos; Imunomodulador; Micropartículas; HPMC; Poloxâmero 188; Spray-drying; Sistema de liberação modificada; Terapias biológicas; Sistema imunológico; Polypeptides; Immunomodulator; Microparticles; HPMC; Poloxamer 188; Spray-drying; Modified release system; Biological therapies; Immune system; CNPQ::CIENCIAS DA SAUDE::FARMACIA